Changes in Ocular Surface Characteristics after Switching from Benzalkonium Chloride-Preserved Latanoprost to Preservative-Free Tafluprost or Benzalkonium Chloride-Preserved Tafluprost. (2nd August 2017) - Tokuda, Naoto; Kitaoka, Yasushi; Matsuzawa, Akiko; Tsukamoto, Ayaka; Sase, Kana; Sakae, Shinsuke; Takagi, Hitoshi
Abstract : Purpose . The aim of the present study was to examine the effects of switching from Latanoprost ophthalmic solution containing a preservative to preservative-free Tafluprost ophthalmic solution or Tafluprost containing a preservative on ocular surfaces. Materials and Methods . Forty patients (40 eyes) with glaucoma (mean age: 62.0 ± 10.9 years) using Latanoprost with preservative for six months or longer were assigned either to a Tafluprost-containing-preservative group (20 eyes) or preservative-free-Tafluprost group (20 eyes). The intraocular pressure, corneal epithelial barrier function (fluorescein uptake concentration with fluorophotometer FL-500), superficial punctate keratopathy (AD classification), and tear film breakup time (TBUT) were assessed before switching and at 12 weeks after switching. Results . No significant differences in intraocular pressure were noted after switching in either group. Corneal epithelial barrier function was improved significantly after switching in both the Tafluprost-containing-preservative and the preservative-free-Tafluprost groups. There were no significant differences in AD scores after switching in the Tafluprost-containing-preservative group, but significant improvements were noted in the preservative-free-Tafluprost group. No significant differences in TBUT were noted in the Tafluprost-containing-preservative or preservative-free-Tafluprost groups after switching. Conclusion . After switching from preservative Latanoprost to Tafluprost containing-preservative or preservative-free Tafluprost, corneal epithelial barrier function was improved while the intraocular pressure reduction was retained.